2014
DOI: 10.1097/igc.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Atl

Abstract: The silence of ARHI expression in vitro seems to accelerate the malignant transformation of healthy ovarian cells by restraining apoptosis and autophagy. The overexpressed ARHI in TOV112D cancer cells suppresses the activation of PI3K/AKT and reduces the expression of Bcl-2, leading to enhanced cell apoptosis and autophagic cancer cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…One of the main genes predicted to be affected and to affect downstream gene expression was the DIRAS3 tumour suppressor. DIRAS3 is a GTPase belonging to the Ras superfamily and shares 50-60% homology with Ras and Rap, two other small GTP binding proteins, whose expression is reported to be reduced in 70% of invasive breast cancers (45,46) and 60% of ovarian cancers (47)(48)(49). DIRAS3 expression was markedly increased in PC3 miR-221del cells at gene and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main genes predicted to be affected and to affect downstream gene expression was the DIRAS3 tumour suppressor. DIRAS3 is a GTPase belonging to the Ras superfamily and shares 50-60% homology with Ras and Rap, two other small GTP binding proteins, whose expression is reported to be reduced in 70% of invasive breast cancers (45,46) and 60% of ovarian cancers (47)(48)(49). DIRAS3 expression was markedly increased in PC3 miR-221del cells at gene and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these results indicated that the cilostazol protected myocardial I/R injury via activating TFEB, which was consistent with a previous study, although with distinct mechanism . It should be also mentioned that exaggerated autophagy may also promote heart failure development .Therefore, maintaining the hemostasis of autophagy is important for cardiac homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in HeLa cells, PI3K/AKT lies upstream of the Bcl-2 and can regulate its expression 35. Li et al found that ARHI can trigger PI3K/AKT pathway to modulate the expression of Bcl-2, and overexpressed ARHI could reduce the phosphorylation of AKT and increase the levels of PI3K inhibitor LY294002 to suppress the expression of Bcl-2 in epithelial ovarian cancer cells 36. This study found that overexpression of ARHI could reduce the protein expression of Bcl-2 to induce apoptosis in ECA109 cells.…”
Section: Discussionmentioning
confidence: 99%